HEALTH PROMOTION IN OLDER AGE GROUPS AS AN OBJECTIVE OF THE SENIOR POLICY: EUROPEAN CHALLENGES - Marzec, Arkadiusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Successful ageing is understood to mean a satisfactory health status, high level of financial independence, firm family and social ties and opportunities for self-realization. The best form of health promotion among the elderly is to promote physical activity. Physical and recreational health-oriented activity and prevention of diseases helps improve physical endurance and strength, and increase muscle mass, flexibility and overall motor coordination. Adequate level of physical exercise at older age effectively prevents ageing processes and ensures maintaining good psychophysical fitness, thus stimulating social integration. The study presents selected forms of recreational forms of physical activity of older adults in local environments resulting from the needs of this group of people and initiatives of local self-governments to promote health.